Does innovation affect the firm performance in developing countries? A conceptual framework - Waris Ali Khan,; Ramraini Ali Hassan,; Syed Azizi Wafa,; Arshad, Muhammad Zulqarnain (Penerbit Universiti Kebangsaan Malaysia, 2020)
The main objective of the paper is to explore the relationships between innovation, entrepreneurial orientation (EO), organizational culture (OC), strategic orientation (SO) and firm performance (FP). Based on the literature review, a conceptual model has been developed of the relationships between variables. This study was greatly motivated by the inconsistent findings and the gaps indicated in the contemporary literature regarding those relationships that have not been developed together within the context of developing countries. This study adopted the resource-based view and contingency theory as an underpinning theory for its assumptions and to develop the theoretical model for this study. To explore the mediating impact of innovation on the relationship between EO, OC, SO and FP in emerging countries. The originality of the article is that it offers valuable implications for different types of firms thus to provide an understanding of the relationship between EO, OC and SO and innovation to introduce innovative processes and products as well as to boost FP.